Plasma membrane density of GABA(B)-R1a, GABA(B)-R1b, GABA-R2 and trimeric G-proteins in the course of postnatal development of rat brain cortex - Dlouhá, K; Kagan, D; Roubalová, L; Ujčíková, H; Svoboda, P (Physiological research, 2013)
With the aim to understand the onset of expression and developmental profile of plasma membrane (PM) content /density of crucial components of GABA(B)-R signaling cascade, GABA(B)-R1a, GABA(B)-R1b, GABA(B)-R2, G(i)1/G(i)2alpha, G(i)3alpha, G(o)alpha, G(z)alpha and Gbeta subunit proteins were determined by quantitative immunoblotting and compared in PM isolated from brain cortex of rats of different ages: between postnatal-day-1 (PD1) and 90 (PD90). PM density of GABA(B)-R1a, GABA(B)-R2, G(i)1/G(i)2alpha, G(i)3alpha, G(o)alpha, G(z)alpha and Gbeta was high already at birth and further development was reflected in parallel decrease of both GABA(B)-R1a and GABA(B)-R2 subunits. The major decrease of GABA(B)-R1a and GABA(B)-R2 occurred between the birth and PD15: to 55 % (R1a, **) and 51 % (R2, **), respectively. Contrarily, PM level of the cognate G-proteins G(i)1/G(i)2alpha, G(i)3alpha, G(o)alpha, G(z)alpha and Gbeta was unchanged in the course of the whole postnatal period of brain cortex development. Maturation of GABA(B)-R cascade was substantially different from ontogenetic profile of prototypical plasma membrane marker, Na, K-ATPase, which was low at birth and further development was reflected in continuous increase of PM density of this enzyme. Major change occurred between the birth and PD25. In adult rats, membrane content of Na, K-ATPase was 3-times higher than around the birth.
Keywords: GTP-Binding Protein alpha Subunits, Gi-Go; Animals; proteiny vázající GTP - beta-podjednotky; Rats; Sodium-Potassium-Exchanging ATPase; Age Factors; receptory GABA-B; GTP-Binding Protein alpha Subunit, Gi2; věkové faktory; proteiny vázající GTP - alfa-podjednotky; proteiny vázající GTP - alfa-podjednotka Gi2; proteiny vázající GTP - alfa-podjednotky Gi-Go; Receptors, GABA-B; GTP-Binding Protein alpha Subunits; krysa rodu Rattus; mozková kůra; Cerebral Cortex; GTP-Binding Protein beta Subunits; zvířata; Heterotrimeric GTP-Binding Proteins; buněčná membrána; heterotrimerní G-proteiny; sodíko-draslíková ATPasa; Cell Membrane